2011
DOI: 10.1017/s1751731110001606
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship between milk urea nitrogen and reproductive performance in Holstein dairy cows

Abstract: The objective of this study was to describe the genetic and phenotypic relationship between milk urea nitrogen (MUN) and reproductive traits in Iranian Holstein dairy cows. Test-day MUN data obtained from 57 301 dairy cows on 20 large dairy herds in Iran between January 2005 and June 2009. Genetic parameters for MUN and reproductive traits were estimated with a five-trait model using ASREML program. Random regression test-day models were used to estimate heritabilities separately for MUN from first, second and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
3
5
3
Order By: Relevance
“…In general, the averages of DO and CI were within the range of values reported in some studies (GonzalezRecio and Alenda, 2005;Zink et al, 2011), the average of DFS in the current study was greater than corresponding averages reported by other researchers (Andersen-Ranberg et al, 2005;Sun et al, 2010;Ghavi Hossein-Zadeh and Ardalan, 2010;Zink et al, 2011). The univariate estimates of CE heritability were slightly greater than those reported by Alday and Ugarte (1997) and Lee et al (2003) in Holsteins, and were similar to estimates reported by Niskanen and Juga (2003) in Ayrshire dairy cows for direct heritability, and smaller than those reported by Abdullahpour et al (2006) and Eghbalsaied et al (2012) in Holsteins, Carnier et al (2000) and Albera et al (2004) Gredler et al (2007) for DO and CI, and by Koeck et al (2010) in Austrian Fleckvieh (Simmental) dual-purpose cattle for DFS.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In general, the averages of DO and CI were within the range of values reported in some studies (GonzalezRecio and Alenda, 2005;Zink et al, 2011), the average of DFS in the current study was greater than corresponding averages reported by other researchers (Andersen-Ranberg et al, 2005;Sun et al, 2010;Ghavi Hossein-Zadeh and Ardalan, 2010;Zink et al, 2011). The univariate estimates of CE heritability were slightly greater than those reported by Alday and Ugarte (1997) and Lee et al (2003) in Holsteins, and were similar to estimates reported by Niskanen and Juga (2003) in Ayrshire dairy cows for direct heritability, and smaller than those reported by Abdullahpour et al (2006) and Eghbalsaied et al (2012) in Holsteins, Carnier et al (2000) and Albera et al (2004) Gredler et al (2007) for DO and CI, and by Koeck et al (2010) in Austrian Fleckvieh (Simmental) dual-purpose cattle for DFS.…”
Section: Discussionsupporting
confidence: 82%
“…The Interbull guidelines (Interbull, 2001) stated that an animal model is better than a sire model and a multiple-trait model is better than a single-trait model. Genetic parameters have been estimated for dystocia (Abdullahpour et al, 2006;Eghbalsaied et al, 2012), productive (Ghavi Hossein-Zadeh, 2011) and reproductive traits (Toghiani-Pozveh, 2009;Ghavi Hossein-Zadeh and Ardalan, 2010;Ghavi Hossein-Zadeh, 2011;Ghiasi et al, 2011) in Iranian Holstein cows. Nevertheless, the estimates of genetic correlations between dystocia and performance traits were scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Average CI, DFS and DO were 403.69, 98.83 and 128.72 days respectively. The average of DO in the current study was lower than the results of the previous studies (Ghavi Hossein‐Zadeh, ; Ghavi Hossein‐Zadeh and Ardalan, ). Also, Ghavi Hossein‐Zadeh () reported greater interval from first to second calving (414 days) in Iranian Holsteins.…”
Section: Resultscontrasting
confidence: 93%
“…Also, Ghavi Hossein‐Zadeh () reported greater interval from first to second calving (414 days) in Iranian Holsteins. Average DFS reported in this study was generally greater than the reports of Ghavi Hossein‐Zadeh and Ardalan () and Mitchell et al. ().…”
Section: Resultscontrasting
confidence: 74%
“…Therefore, the use of correlated traits may be beneficial for the selection process. Genetic relationships of MUN with fitness traits, such as reproductive performance and health, have been under investigation (Mitchell et al 2005 ; König et al 2008 ; Hossein-Zadeh and Ardalan 2011b ; Mucha and Strandberg 2011 ). The estimation of genetic correlations with diseases is currently not possible, as this kind of data is not recorded in Poland.…”
Section: Introductionmentioning
confidence: 99%